MADZHAB HUKUM ISLAM - Sheila Fakhria (Institut Agama Islam Tribakti (IAIT) Kediri, 2015)
The school of law are determined by law and the period of time so that by jurists make legal interpretation based on the time and place. So at this time jurists are always reviewing the law that is based on the presence or emergence of various schools in the philosophy of law shows the struggle of ideas will not cease in the field of law. Similarly, the existence of Islamic law in a society that seeks to be grouped according typology of existing law schools in the philosophy of law.